2022
DOI: 10.3389/fcvm.2022.993617
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and novel tobacco products drive adverse cardiac remodeling and dysfunction in preclinical studies

Abstract: BackgroundThe heart undergoes structural and functional changes in response to injury and hemodynamic stress known as cardiac remodeling. Cardiac remodeling often decompensates causing dysfunction and heart failure (HF). Cardiac remodeling and dysfunction are significantly associated with cigarette smoking. Although cigarette smoking has declined, the roles of nicotine and novel tobacco products (including electronic cigarettes and heat-not-burn tobacco) in cardiac remodeling are unclear. In this perspective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Additionally, in their longitudinal analyses, participants who were currently smoking showed a significant increase in left ventricular mass index, with both an increase in left ventricular wall thickness and end-diastolic diameter; whereas, LV end-diastolic diameter decreased among participants who did not smoke, consistent with aging-associated concentric remodeling [41]. Recently, Fried et al showed a phenotypic shift from concentric hypertrophy to eccentric hypertrophy in nicotine-exposed, hemodynamically-stressed mice [78]. Thus, higher central aortic pressure and enhanced wave reflection in the setting of smoking may contribute to eccentric remodeling and subsequent decompensation to incident CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in their longitudinal analyses, participants who were currently smoking showed a significant increase in left ventricular mass index, with both an increase in left ventricular wall thickness and end-diastolic diameter; whereas, LV end-diastolic diameter decreased among participants who did not smoke, consistent with aging-associated concentric remodeling [41]. Recently, Fried et al showed a phenotypic shift from concentric hypertrophy to eccentric hypertrophy in nicotine-exposed, hemodynamically-stressed mice [78]. Thus, higher central aortic pressure and enhanced wave reflection in the setting of smoking may contribute to eccentric remodeling and subsequent decompensation to incident CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Higher central pulse pressure increases afterload and may alter cardiac geometry maladaptively as concentric remodeling for individuals who smoke [71][72][73][74][75]. While the traditional view relates elevated central pressure with concentric remodeling due to pressure overload, animal studies have shown that smoking or nicotine exposure contributes to eccentric or mixed cardiovascular remodeling patterns [76][77][78]. Similar to the current study, Markus et al observed in two separate cohorts that participants who were currently smoking had higher mean central systolic blood pressure, augmentation index, and left ventricular mass compared to participants who did not smoke [41].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that we are not suggesting that nicotine has no influence or effect on the cardiovascular system (see review [ 47 ]). Indeed, recent preclinical studies in mice creating aerosolized nicotine by bubbling free-base nicotine with air (at a concentration similar to smokers and vapers) have found changes in blood pressure and cardiac remodeling [ 48 , 49 ]. Moreover, evidence from animal embryo models has revealed the greater incidence and severity of cardiac defects with nicotine exposure with E-cig aerosol or cigarette smoke extracts [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The full spectrum of physiological responses to individual vape aerosol constituents continues to be revealed by ongoing investigation, but nicotine has been studied for decades with extensive reviews of cumulative literature. [24][25][26][27][28][29] Many studies were conducted in the context of smoking tobacco, rendering conclusions on the impact of nicotine impossible to completely dissociate from the multitude of other chemical compounds in cigarette smoke. Nevertheless, nicotine alone exerts very profound and specific actions, including alteration of wound healing and inflammation [30][31][32] , fibrosis with collagen deposition [33][34][35] , physiological effects on the cardiovascular system 24,36,37 , as well as cellular and molecular changes in cardiovascular and pulmonary tissues.…”
Section: Introductionmentioning
confidence: 99%